2010
DOI: 10.1063/1.3325033
|View full text |Cite
|
Sign up to set email alerts
|

A high-reflectivity atom-focusing mirror stable at room temperature

Abstract: It is shown that the Pb(√3×√3)R30/Si(111) ordered layer is an excellent mirror for neutral He atoms. It focuses more than 15% of the incoming He atoms into the specular peak, and is stable up to 450 K. Moreover, the reflectivity remains almost unchanged in a time scale of several weeks in ultrahigh vacuum. As a consequence, this system is a very good candidate to be used as a mirror in the next generation of the scanning helium atom microscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The lack of any loss of the beam to diffuse reflection from a mirror is only one factor in this. Mirror experiments by Barredo et al 11,12 indicated a count rate (presumably detector counts) of somewhat under 10 7 per second, but it is difficult to relate this to the atom intensity at a given spot size. One would presume that in time focusing methods can achieve higher inten-sities than pinhole optics, but this does not currently appear to be the case.…”
Section: A Sourcementioning
confidence: 99%
“…The lack of any loss of the beam to diffuse reflection from a mirror is only one factor in this. Mirror experiments by Barredo et al 11,12 indicated a count rate (presumably detector counts) of somewhat under 10 7 per second, but it is difficult to relate this to the atom intensity at a given spot size. One would presume that in time focusing methods can achieve higher inten-sities than pinhole optics, but this does not currently appear to be the case.…”
Section: A Sourcementioning
confidence: 99%
“…6 Quantum-stabilized Pb films on Si(111) 8 and Pb(H3 Â H3)R30/Si(111) surfaces 9 provide high specular He reflectivity ($15%) but are only stable in ultrahigh vacuum (UHV). We have recently shown that monolayer graphene (MLG) on Ru(0001) single crystals can provide an inert surface 10,11 with high reflectivity for thermal He and H 2 beams.…”
mentioning
confidence: 99%